Exposure to parent assault on a sibling as a childhood adversity. (December 2021) - Tucker, Corinna Jenkins; Finkelhor, David; Turner, Heather
Abstract: Background: Children's exposure to parental violence against another parent has been widely studied as an adverse childhood experience and source of childhood trauma. Exposure to parental violence against a sibling could be equally as traumatizing, but the literature on this exposure is sparse, by comparison. We examined the frequency of exposure to parental assault on a sibling (EPAS) and its demographic distributions. We also investigated the links between EPAS and symptoms of distress. Method: From three combined surveys of the National Survey on Children's Exposure to Violence, based on telephone interviews with parents, and in the case of those 10–17 years old, adolescents, we examined children living with a juvenile sibling ( N  = 7, 029; 49% female). Results: Lifetime EPAS was 3.7%, and sibling assault was more common by fathers (70%) than by mothers (30%). Exposure was greatest for boys and adolescents, highest for those whose parents had some college education, and for those living with other non-parental adults, single parents, and stepfamilies. Rates did not differ by ethnicity. Most exposed youth felt afraid (83%), and fear was greater when witnessing fathers than mothers assaulting a sibling. Controlling for child maltreatment and exposure to interparental violence, those exposed to EPAS showed higher current levels of mental distress (anger, depression, and anxiety; F (10, 6146) = 140.44, p  = .001; R 2  = 0.19). Conclusions: Clinical work and parent education programs should address the occurrence of EPAS and the adverse association between EPAS and mental health to reduce its potential negative impact.